The role of Pax6 isoforms in embryonic development - Pinson, Jennifer (The University of Edinburgh, 2005)
During murine development, organogenesis of the central nervous system is a tightly controlled process. Complex regulatory gene networks exist, at the head of which are transcription factors that affect the expression of downstream genes. One such transcription factor, Pax6, is crucial for the correct development of a number of organs, including the brain, eyes and spinal cord.

A number of Pax6 isoforms have been described, many of which involve alterations to the two DNA-binding domains, the paired domain and the homeodomain. In the best characterised of these isoforms, Pax6+5a, the insertion of a 42bp cassette exon by alternative splicing leads to the disruption of a helix-turn-helix motif within the paired domain. The DNA-binding specificity of the Pax6 protein is changed, thereby altering the target genes on which Pax6 can act. Other isoforms exist in which the entire paired domain is absent, and DNA-binding can only occur via the homeodomain.

In this way, numerous transcription factors are derived from the Pax6 locus, all of which are predicted to have the same transactivation properties, but which act on different subsets of downstream genes

The aims of this study were i) to characterise differences in the spatial and temporal expression of Pax6 isoforms during murine embryonic development ii) to analyse the expression of Pax6 isoforms in various Pax6 mutant mice during neurogenesis, and iii) to examine the effects of over-expression of the best understood isoforms, in a cell culture system. The overall aim was to elucidate the independent roles of Pax6 isoforms in organogenesis of the central nervous system.

RNase protection assay was used to determine the ratio between Pax6 and Pax6+5a transcripts in a number of tissues of the central nervous system during neurogenesis. In most tissues studied, Pax6 is much more prevalent than Pax6+5a at embryonic day 12.5, but the ratio has fallen by embryonic day 18.5. This may be indicative of a change in the role of Pax6, from controlling proliferation to controlling neuronal differentiation.

Pax6 protein expression was analysed in mice with 0, I, 2, 8 and 14 functional copies of Pax6, in order to compare the levels of Pax6 expression between genotypes, and to determine if differential expression of one or more isoforms could be responsible for the mutant phenotypes. Most isoforms are down-regulated in the Pax6Sey/+ eye, whilst their relative expression is more varied in the Pax6ey/+ brain. Most isoforms are significantly up-regulated in the brain and eye of mice with 8 or 14 copies of Pax6, but there are no differences between expression levels in the brain of the two genotypes, indicating that Pax6 is subject to autoregulation. Some Pax6 isoforms are observed in the brain of mice thought to lack functional Pax6.

Expression constructs containing Pax6, Pax6+5a and "paired-less" Pax6 were introduced into immortalised cell lines. Again, Pax6 autoregulation was demonstrated; the over-expression ofPax6 leads to the up-regulation of Pax6+5a, and vice versa. Pax6 over-expression also promotes neuronal differentiation in a neuroblastoma-derived cell line.